The Effect of Nano Technology Liquid Organic Fertilizer on the Growth of Kailan (Brassica oleraceae var. alboglabra) Grown - Roisiah, Qoimatun; Fevria, Resti (Jurnal Serambi Biologi, 2023)
Kailan (Brassica oleraceae var. alboglabra) is a vegetable commodity that has nutritional content for public consumption in fulfillment of nutrition. Kailan plants can be cultivated hydroponically. The disadvantage of hydroponic cultivation is the occurrence of nutrient deposition, especially in the axis system, where the nutrient water does not move. Techniques that can reduce the amount of nutrient deposition that occurs in hydroponic systems are needed given this problem. Nanotechnology is one of the technologies being developed. This research was conducted using the RAL method (completely randomized design) which consisted of 6 treatments and 4 replications and namely Control (Well Water + AB Mix), P1 (Nano-technology Water + 100% AB Mix), P2 (Nano-technology Water + 25 % POC+75% AB Mix), P3 (nano technology water+50% POC+50% AB Mix), P4 (nano technology water+75% POC+25% AB Mix), P5 (nano technology water+100% POC ). The results of this study are the effect of the use of liquid organic fertilizer nano technology on the growth of kailan which can be seen in the tallest plants which can be seen in P1 with a plant height of 23.10 cm, the highest number of leaves in P2 with 12.50 strands, the highest leaf area in P1 with an area of 17,6000 cm², the highest wet weight was in P1 of 11.84 g, and the highest dry weight was in P1 of 1.06 g. The use of liquid organic fertilizer with nano technology has an influence on the growth of kailan cultivated hydroponically.